FORMULATION AND EVALUATION OF HERBAL SOAP TAKING DIFFERENT BIOACTIVE PLANTS BY COLD SAPONIFICATION METHOD - SHARMA, SAFAL; PRADHAN, SUSHILTA; PANDIT, BIBHAS; MOHANTY, JYOCHHANA PRIYA (International Journal of Current Pharmaceutical Research, 2022)
Objective: The final goal of this research is to develop and evaluate herbal bath soap taking various bioactive herbal plants extract with different ethinic and dermatological importance in ayurveda, namely Solanum lycopersicum, Sapindus mukorossi, Acacia nilotica, Citrus limon, Aloe barbadensis, Piper betle, Curcuma longa and Cocus nucifera. Methods: The extract of all plant materials were obtained through various extraction procedures suitable for them. The extract was then mixed with lye and fatty oil for preparing a soap using the cold saponification method. Results: The prepared soap was evaluated against marketed soap. The prepared soap was found to be good in appearance, color and odor. pH, % free alkali content, foamability, foam stability, moisture content and alcohol insoluble matter were found to be 9.6, 0.22, 15 cm, 14.5 cm, 3.26 and 17.25, respectively. The antioxidant activity and antibacterial studies were done, which signifies prepared soap to be a potent antioxidant and antibacterial source. Conclusion: Based on the study results it can be concluded that herbal soap can be formulated using cold process method, taking different parameters in consideration as that of skin condition and as that of herbal potentials and its activity. This sought of herbal formulation can bring a big difference in the field of herbal cosmetic as there are many alignment and related flaws in different polyherbal or chemical-based formulations which can be removed.